Clinical and biochemical polymorphism of spinal muscular atrophy - M. G. Sokolova; S. V. Lobzin; I. V. Litvinenko; M. V. Rezvantsev; L. A. Polyakova (Неврология, нейропсихиатрия, психосоматика)
Objective: to conduct clinical laboratory studies of spinal muscular atrophy (SMA) for the clarification of the pathogenetic features and role of neurotrophic factors in the formation of polymorphism of this diseasePatients and methods. Thirty-five patients aged 9 months to 53 years (mean age, 14.5 years) with different inherited forms of SMA were examined. Clinical, genealogical, and laboratory tests were carried out. A control group consisted of 40 healthy individuals aged 7–45 years (mean age, 16.5 years). The levels of neurotrophins, such as brain-derived growth factor (BDGF), nerve growth factor (NGF), and ciliary neurotrophic factor (CNTF) in serum samples were determined by enzyme immunoassay.Results. Changes in the expression of the neurotrophic factors were found in patients with SMA. The enzyme immunoassay data suggest that the serum concentrations of BDGF, NGF, and CNTF in patients with SMA were significantly higher than those in healthy controls. The group of SMA patients aged under 18 years showed a statistically significant (p<0.001) increase in NGF concentrations (3680±936 ng/ml) versus the control group of the same age (625±444 pg/ml).Conclusion. In our opinion, the clinical polymorphism of SMA can be explained by the polymorphism of various pathogenic factors: genetic, morphofunctional, and biochemical ones. Overexpression of neurotrophins was first noticed to play a role in the development of more severe clinical types of SMA (proximal SMA), which may be related to both the ontogenetic features of children's age and disease duration. The study results can be further used to choose pathogenetic personalized therapy for SMA.